2010
DOI: 10.1071/wr09072
|View full text |Cite
|
Sign up to set email alerts
|

Management of animal and plant pests in New Zealand - patterns of control and monitoring by regional agencies

Abstract: Context. Significant resources are spent annually in New Zealand controlling pests to mitigate impacts on native biodiversity and agricultural production, but there are few reliable estimates of the benefits. Concerns have been expressed about inconsistent monitoring methodologies, differing frequencies and intensities of control across organisations, and poor definition of desired outcomes. Aims. To conduct and report on a survey of animal and plant pest control and monitoring by regional agencies, to identif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 10 publications
0
25
0
Order By: Relevance
“…The global cost of monitoring and controlling these predators is in the order of hundreds of millions, if not billions, of dollars annually (e.g. Clayton and Cowan, 2010;Gong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The global cost of monitoring and controlling these predators is in the order of hundreds of millions, if not billions, of dollars annually (e.g. Clayton and Cowan, 2010;Gong et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, relatively few studies have quantified the responses of indigenous biota (both species and ecological processes) in natural ecosystems. This may be because insufficient resources are allocated for monitoring (Clayton and Cowan, 2010;Reddiex and Forsyth, 2006) or because techniques are inadequate (de Bello et al, 2010). Baxter et al (2008) developed a theoretical model that examined the cost-effectiveness of controlling pest predators, and concluded that suppression of predator abundance to a 'pre-determined limit' (or threshold) can be a more cost-effective strategy than eradication.…”
Section: Introductionmentioning
confidence: 99%
“…The potential exists in New Zealand for community data to contribute to larger monitoring programmes given current shortfalls in agency-led monitoring (Clayton & Cowan 2010). For example, limited outcome monitoring being conducted on possum (Trichosurus vulpecula) control operations by resource management agencies (Clayton & Cowan 2010) could be supplemented by data from community groups, as large numbers of groups trap possums and other predators on council-owned land (Peters et al 2015).…”
Section: Data Usementioning
confidence: 99%